Open Source Software User Communities: A Study of Participation in Linux User Groups - Bagozzi, Richard P.; Dholakia, Utpal M. (Management Science, 2006)
We conceptualize participation in Linux user groups (LUGs) in terms of group-referent intentional actions and investigate cognitive (attitudes, perceived behavioral control, identification with the open source movement), affective (positive and negative anticipated emotions), and social (social identity) determinants of participation and its consequences on Linux-related behaviors of users. This survey-based study, conducted with 402 active LUG members representing 191 different LUGs from 23 countries and employing structural equation modeling methodology, supports the proposed model. Furthermore, we find that the Linux user’s experience level moderates the extent of the LUG’s social influence and its impact on the user’s participation. We conclude with a consideration of the managerial and research implications of the study’s findings.